Cover Image, Volume 85, Issue 2. Issue 2 (February 2017) - Anjos, Liliana; Morgado, Isabel; Guerreiro, Marta; Cardoso, João C. R.; Melo, Eduardo P.; Power, Deborah M.
Abstract : The cover image, by Isabel Morgado et al., is based on the Article Cartilage acidic protein 1, a new member of the beta‐propeller protein family with amyloid propensity, DOI:10.1002/prot.25210 .